Hemodynamic Analysis of Pediatric Septic Shock and Cardiogenic Shock Using Transpulmonary Thermodilution. (16th March 2017) - Lee, En-Pei; Hsia, Shao-Hsuan; Lin, Jainn-Jim; Chan, Oi-Wa; Lee, Jung; Lin, Chia-Ying; Wu, Han-Ping
Abstract : Septic shock and cardiogenic shock are the two most common types of shock in children admitted to pediatric intensive care units (PICUs). The aim of the study was to investigate which hemodynamic variables were associated with mortality in children with shock. We retrospectively analyzed 50 children with shock (37 septic shock cases and 13 cardiogenic shock cases) in the PICU and monitored their hemodynamics using transpulmonary thermodilution from 2003 to 2016. Clinical factors were analyzed between the patients with septic and cardiogenic shock. In addition, hemodynamic parameters associated with mortality were analyzed. The 28-day mortality was significantly higher in the septic group than in the cardiogenic group (p = 0.016 ). Initially, the parameters of cardiac output and cardiac contractility were higher in the septic group (p < 0.05 ) while the parameters of preload and afterload were all higher in the cardiogenic group (p < 0.05 ). Cardiac index was significantly lower in the nonsurvivors of cardiogenic shock at the time of initial admission and after the first 24 hours (both p < 0.05 ), while systemic vascular resistance index (SVRI) was significantly lower in the nonsurvivors of septic shock (p < 0.001 ). Therefore, during the first 24 hours after intensive care, SVRI and cardiac index are the most important hemodynamic parameters associated with mortality.